Contract farming in Gallo municipality (A development vision for semi-urban farms) - Al-Akaf, JADALLA ALI; Elduhere, Ibrahim Ali (Journal of agricultural, environmental and veterinary sciences, 2023)
Contract farming may be defined as agricultural production carried out according to a prior agreement in which the farmer commits to producing a given product in a given manner and the buyer commits to purchasing it, and therefore contract farming reduces risk and uncertainty for both parties as compared to buying and selling crops on the open market. Therefore, this paper investigates how the Contract farming application in semi-urban farms of Gallo municipality, a total of ninety-two questionnaires were distributed to farmers where 80 responded. A quantitative data analysis approach was used to analyze the data (SPSS). The results indicated that there are benefits to contract farming. Finally, the study recommended that by issuing legislation for incentives and controls for contract farming.
Keywords: Contract farming; semi-urban farms; problems; benefits; suggestions